She is no Desdemona: a Syrian woman in Samar Attar's Shakespearean subversions. Issue 2 (2nd September 2018) - Alhawamdeh, Hussein A.
ABSTRACT: This paper analyzes the significance of appropriating three plays by William Shakespeare— Macbeth (1606), Romeo and Juliet (1597), and Othello (1604)—in Samar Attar's Lina: A Portrait of a Damascene Girl . The Syrian novelist, Attar, finds in Shakespeare powerful sites for the expression of exile, rejection of sentimental love, and resistance of patriarchy in Arab societies. Attar's reading of Shakespeare is both constructive and deconstructive. Her novel shows simultaneously identification with and challenges to the British Bard. The main female protagonist, Lina, renounces Shakespeare's dramatization of the concept of love in Romeo and Juliet and Othello, which requires the female submission to the authority of the male lover. In Macbeth, Attar identifies with its concepts of exile and homeland when one's country becomes polluted by political conspiracies and chaos. Lina, in Attar's novel, is a new Arab Desdemona/Juliet, who is subversive and revolutionary to the atrocities of gender marginalization.